Short Communication Development and Evaluation of Combined Wavelet Based Palmprint Identification System: Short Communication: Palmprint Identification System - Mansoor, Atif Bin; Masood, Hassan; Mumtaz, Mustafa; Khan, Shoab Ahmad (Biological Sciences - PJSIR, 2019)
Palmprint based identification is fairly recent biometric modality gaining popularity due to its traits like user comfort, reliability and easy acquisition. A wavelet based palmprint identification system has been proposed. Euclidean distance based classification is performed using Biorthogonal, Symlet and Discrete Meyer wavelets on 500 palmprints obtained from 50 users for individual and combined features, employing locally developed acquisition platform. An equal error rate (EER) of 0.0217 and genuine acceptance rate (GAR) of 97.12% demonstrate the effectiveness of the combined system.